Thermomigration of non-oriented aluminium-rich liquid zones through (110) silicon wafers - Оlекsіі Polukhin; Vitalii Kravchina (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The paper analyzes the reasons and factors that allow avoiding faceting of non-oriented linear zones. It is shown that in the manufacture of semiconductor chips with a large perimeter and a reverse voltage of 2000 V, the conditions sine qua non to create isolating walls on silicon wafers with an orientation different from (111) are to form an ensemble of linear zones by the method of high-temperature selective forced wetting (HSV) and to fulfill a number of requirements to the “thermomigration” photomask and zones immersion stage during TM at high temperatures. It is shown that these factors provide a stable migration of an ensemble of linear zones through wafers (110) even in a stationary temperature gradient field. For the first time in the world, the authors practically demonstrate the possibility of stable migration of an ensemble of non-oriented linear zones through silicon (110) in a stationary temperature gradient conditions, outlining the conditions and factors necessary for this process. It is assumed that when the conditions for the formation of linear zones and their immersion are met, the crystallographic orientation of the silicon wafers does not matter at all.